Facial plating industry payments: An analysis of the open payments database - F. Jeffrey Lorenz; Brandon LaBarge; Jessyka G. Lighthall; Scott G. Walen (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objective To compare industry payments from facial plating companies to plastic surgery, oral and maxillofacial surgery (OMFS), and otolaryngology (OHNS). Methods The Open Payments Database was queried from 2016 to 2021 to identify all industry disbursements related to facial plating products from Stryker, Zimmer Biomet, Depuy Synthes Products, Acumed, and KLS Martin. Total dollars, number of payments, and specialists paid were compared between plastic surgery, OMFS, and OHNS. Funding was correlated to estimated case volume and number of licensed surgeons determined by literature review. Results From 2016 through 2021, OMFS received an average of $786,497 annually, followed by plastic surgery ($765,482), and OHNS ($184,484). On average, facial plating companies distributed 2256, 963, and 917 yearly payments to 699 oral and maxillofacial surgeons, 378 plastic surgeons, and 354 otolaryngologists, respectively. Total dollars, number of payments, and specialists paid were significantly different between specialties (p < .05). Facial trauma coverage is 39.6% by plastic surgery, 36.6% by OMFS, and 23.3% by OHNS. There are 7560 licensed oral and maxillofacial surgeons, 4948 plastic surgeons, and 11,778 otolaryngologists in the United States. Decreased payment to OHNS was more than could be accounted for by case volume alone. Conclusions The facial plating industry allocates more funding dollars to OMFS and plastic surgery compared to OHNS. OMFS receives the greatest number of payments to the most specialists compared to plastic surgery and OHNS. Engagement between OHNS and the facial plating industry is a potential area of growth in the future. Level of evidence: Level 4.